RUANG PERMUKIMAN DI DESA TENGANAN DAUH TUKAD SEBAGAI WADAH PELESTARIAN BUDAYA DAN PENGGERAK EKONOMI LOKAL - SILANTARA, I GEDE GANDHI; GANIASIH, NI NYOMAN TITI (GANEC SWARA, 2024)
Tenganan Dauh Tukad Village is one of the Bali Aga villages that still maintains the heritage of ancestral traditions and culture in everyday life. The uniqueness of residential architecture in this village is not only reflected in the layout of buildings, but also in the functional role of these spaces in supporting community cultural activities. This village maintains its traditions by organizing the spatial layout based on the hulu-teben concept, which distinguishes between sacred and profane zones. This research aims to identify and analyze the role of space in Tenganan Dauh Tukad Village as a place for preserving culture and driving the local economy. This research uses a descriptive qualitative method with a case study approach. The results showed that spaces in Tenganan Dauh Tukad Village settlements have a significant role in supporting cultural activities. Spaces such as Bale Agung and other structures not only function as physical places, but also become symbols of togetherness and collective strength in the Tenganan Dauh Tukad community. One of the cultural activities carried out at Bale Agung is the traditional ceremony of Perang Pandan (Screwpine War), which is also a tourist attraction that contributes to the local economy. This research concludes that residential architecture in Tenganan Dauh Tukad Village is not just a place to live, but also serves as an important platform to preserve community culture and support local economic sustainability.